A study of abnormal Calcium Phosphorus Product in Chronic Kidney Disease in Kerala population and its correlation with Acute Coronary Syndrome - Kartik Jadhav; Akash Thomas Oommen (Al Ameen Medical College, 2016)
Objective: To determine the cutoff value for Calcium Phosphorus Product (CPP) in Chronic Kidney Disease (CKD) patients, above which there is a high risk of Acute Coronary Syndrome(ACS). Methods: Ninety five CKD patients on maintenance dialysis [2 to 3 sessions weekly] were followed up at AIMS, Kochi for a period of 2 years and any new onset acute coronary event during the following period were diagnosed and noted. All the relevant biochemical tests were performed including ECG and 2D Echocardiography. Standard statistical tests with multivariate regression analysis and ROC were performed to arrive at conclusion. Results: Out of 95 patients, 28 patients (29.5%) had ACS, with majority number of patients above 50 years of age [27(96.4%)]. Out of 95 patients 25(26.3%) were females and 70(73.7%) males. Out of 25 female patients 6(24%) had ACS. Out of 70 male patients, 22(31.4%) had ACS. The mean CPP was calculated for each patient and grouped into 4 groups [<40mg2/dl2; 40-55; 56-70; >70]. Patients with CPP>70mg2/dl2 had highest incidence of ACS with 92.3% patients involved [Pvalue<0.001]. Patients with CPP>55mg2/dl2 had odds ratio of 18.214 after multivariate regression analysis. ROC curve for CPP showed a cutoff point of 51.4mg2/dl2 with sensitivity of 78.6% and specificity of 73.1% for predicting ACS. Conclusion: This study shows that the cutoff value for CPP above which ACS is common is 51.49mg2/dl2 for the local population, which is quite less than the recommended KDOQI guidelines. Therefore a stricter control among the local population is recommended.